Bioinspired hierarchically structured liquid metal-composited eutectogel for energy conversion and intelligent perception - Yuxi Chen; Gonghua Hong; Xuning Song; Jiali Jiang; Yunhao Zhang; Long Zhao (Chemical Engineering Journal, 2026)

Microbial community structure and function and their linkages with methane production in sediments of thermokarst lakes on the Tibetan Plateau - Yutong Song; Chao Mao; Pengfei Liu; Guibiao Yang; Luyao Kang; Ziliang Li; Wei Zhou; Xuning Liu; Shiting Yao; Yuanhe Yang (Science China Life Sciences, 2026)

Toward tough and recyclable ionogels with high thermal sensitivity via microphase separation for sustainable ionic skins - Jiali Jiang; Xuning Song; Yuxi Chen; Haifeng Zhou; Long Zhao (Chemical Engineering Journal, 2026)

Smart multifunctional hydrogels with synergistic non-covalent networks for transparency-switching-based information encryption and multimodal sensing - Xuning Song; Jiali Jiang; Long Zhao (Chemical Engineering Journal, 2025)

Capture-SELEX-based screening and mechanism analysis for the dual-colorimetric aptasening of microcystin in water - Zhongmei Peng; Xuning Kang; Zhenlin Fan; Jingping Zhang; Yuzhu Song; Jinyang Zhang; Qinqin Han (Analytica Chimica Acta, 2025)

Virus-host interactions and their effects on the prokaryotic community in thermokarst lakes - Yutong Song; Guibiao Yang; Pandeng Wang; Xiaoqing Luo; Jian-Yu Jiao; Zhihu Zheng; Luyao Kang; Dianye Zhang; Ziliang Li; Wei Zhou; Xuning Liu; Lili Han; et al. (Science Bulletin, 2025)

Experimental study on chemiluminescence characteristics in Methane-Oxygen laminar flame affected by DC electric field - Yan Gong; Jingxuan Wu; Yue Wu; Qinghua Guo; Xuning Wang; Xudong Song; Guangsuo Yu (Fuel, 2025)

Generation and resource potential of waste PV modules considering technological iteration: A case study in China - Zishuo Wang; Bo Li; Xiaolong Song; Xuning Zhuang; Wenjie Wu; Ang Li (Environmental Impact Assessment Review, 2025)

Patterns and drivers of prokaryotic communities in thermokarst lake water across Northern Hemisphere - Luyao Kang; Leiyi Chen; Ziliang Li; Jianjun Wang; Kai Xue; Ye Deng; Manuel Delgado‐Baquerizo; Yutong Song; Dianye Zhang; Guibiao Yang; Wei Zhou; Xuning Liu; et al. (Global Ecology and Biogeography, 2023)
Aim The formation of thermokarst lakes could make a large amount of carbon accessible to microbial degradation, potentially intensifying the permafrost carbon‐climate feedback via carbon dioxide/methane emissions. Because of their diverse functional roles, prokaryotes could strongly mediate biogeochemical cycles in thermokarst lakes. However, little is known about the large‐scale patterns and drivers of these communities. Location Permafrost regions in the Northern Hemisphere. Time period Present day. Major taxa studied Prokaryotes. Methods Based on a combination of large‐scale measurements on the Tibetan Plateau and data syntheses in pan‐Arctic regions, we constructed a comprehensive dataset of 16S rRNA sequences from 258 thermokarst lakes across Northern Hemisphere permafrost regions. We also used the local contributions to beta diversity (LCBD) to characterize the variance of prokaryotic species composition and screened underlying drivers by conducting a random forest modelling analysis. Results Prokaryotes in thermokarst lake water were dominated by the orders Burkholderiales, Micrococcales, Flavobacteriales and Frankiales. The relative abundance of dominant taxa was positively associated with dissolved organic matter (DOM) properties, especially for the chromophoric/aromatic compounds. Microbial structure differed between high‐altitude and high‐latitude thermokarst lakes, with the dominance of Flavobacterium in high‐altitude lakes, and the enrichment of Polynucleobacter in high‐latitude lakes. More importantly, climatic variables were among the main drivers shaping the large‐scale variation of prokaryotic communities. Specifically, mean annual precipitation was the best predictor for prokaryotic beta diversity across the Northern Hemisphere, as well as in the high‐altitude permafrost regions, while mean annual air temperature played a key role in the high‐latitude thermokarst lakes. Main conclusions Our findings demonstrate significant associations between dominant taxa and DOM properties, as well as the important role of climatic factors in affecting prokaryotic communities. These findings suggest that climatic change may alter DOM conditions and induce dynamics in prokaryotic communities of thermokarst lake water in the Northern Hemisphere.

Patterns and drivers of anaerobic nitrogen transformations in sediments of thermokarst lakes - Chao Mao; Yutong Song; Yunfeng Peng; Luyao Kang; Ziliang Li; Wei Zhou; Xuning Liu; Futing Liu; Guibing Zhu; Yuanhe Yang (Global Change Biology, 2023)
Significant attention has been given to the way in which the soil nitrogen (N) cycle responds to permafrost thaw in recent years, yet little is known about anaerobic N transformations in thermokarst lakes, which account for more than one‐third of thermokarst landforms across permafrost regions. Based on the N isotope dilution and tracing technique, combined with qPCR and high‐throughput sequencing, we presented large‐scale measurements of anaerobic N transformations of sediments across 30 thermokarst lakes over the Tibetan alpine permafrost region. Our results showed that gross N mineralization, ammonium immobilization, and dissimilatory nitrate reduction rates in thermokarst lakes were higher in the eastern part of our study area than in the west. Denitrification dominated in the dissimilatory nitrate reduction processes, being two and one orders of magnitude higher than anaerobic ammonium oxidation (anammox) and dissimilatory nitrate reduction to ammonium (DNRA), respectively. The abundances of the dissimilatory nitrate reduction genes ( nirK , nirS , hzsB , and nrfA ) exhibited patterns consistent with sediment N transformation rates, while α diversity did not. The inter‐lake variability in gross N mineralization and ammonium immobilization was dominantly driven by microbial biomass, while the variability in anammox and DNRA was driven by substrate supply and organic carbon content, respectively. Denitrification was jointly affected by nirS abundance and organic carbon content. Overall, the patterns and drivers of anaerobic N transformation rates detected in this study provide a new perspective on potential N release, retention, and removal upon the formation and development of thermokarst lakes.

The energy saving and GHG mitigation benefits assessment of product remanufacturing from a multi-life cycle perspective: A case study of spark plug - Xuning Zhuang; Xiaolong Song; Hui Yang; Di Zhao; Wenjie Wu; Jing Zhao (Environmental Impact Assessment Review, 2023)

The Differences in Structure and Function of the Cerebellum Between Cantonese-Mandarin Bilinguals and Mandarin Monolinguals: a Multi-model MRI Study - Yuying Jin; Xiaoxuan Fan; Xiaoyu Xu; Ning Pan; Jin Jing; Xiaojing Song; Si Tan; Xuning Guo; Xiuhong Li (The Cerebellum, 2022)

Nutritional strategy for the preferential uptake of $${{\text{NO}}_{3}}^{ - } {\text{{-}N}}$$ by Phaeocystis globosa - Xuning Lv; Zaixing Wu; Xiuxian Song; Yongquan Yuan; Xihua Cao; Zhiming Yu (Hydrobiologia, 2019)